KONSTELASI HUKUM ADAT DAN HUKUM ISLAM DI MASA PENJAJAHAN - Aiz, Muhammad (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2010)
The modern codification of civil law developed out of the customs, or coutumes of the middle ages, expressions of law that developed in particular communities and slowly collected and later written down by local jurists. Such customs acquired the force of law when they became the undisputed rule by which certain entitlements (rights) or obligations were regulated between members of a community. The Custom of Jawa --the customary law that developed within the city of Jawa-- is an example of custom law. Sharia is derived from the sacred text of Islam (the Qur'an), and Traditions (Hadith) gathered from the life of the Islamic Prophet Muhammad. There are different interpretations in some areas of Sharia, depending on the school of thought (Madh'hab), and the particular scholars (Ulama) involved. Traditionally, Islamic jurisprudence (Fiqh) interprets and refines Sharia by extending it's principles to address new questions. Islamic judges (Qadi) apply the law, however modern application varies from country to country.